Research Status and Prospect of Anti - Friction and Anti - Wear Modification of Silicon Material Surface - CHEN Long, CHEN Wen-gang, XIE Yong, LIU De-chun, SONG Wen-tao (Cailiao Baohu, 2021)
In recent years, micro-electro-mechanical system(MEMS) has been developed rapidly, but the problem of friction and wear between micro-components in which relative motion occurs in the system has not been well resolved, limiting its further widespread application and in-depth development. In this paper, the research status and progress of solid film lubrication, molecular ultra-thin film lubrication, ion implantation, micro texture and graphene film surface modification in anti-friction and anti-wear of MEMS were mainly summarized. It was pointed out that the research on the silicon composite surface modification technology and the friction behavior of modified layer should continue to be deepened, and the innovation and exploration of the new composite surface modification technology should be strengthened. This work could have certain reference significance for the study of extending the service life of MEMS.